Effects of Fireworks Burning on Air Quality during the Chinese Spring Festival—Evidence from Zhengzhou, China - Xinzhan Liu; Ling Yang; Yan Wang; Pengfei Yan; Yimeng Lu (Toxics, 2023)
Fireworks burning significantly degrades air quality over a short duration. The prohibition of fireworks burning (POFB) policy of 2016 and the restricted-hours fireworks burning (RHFB) policy of 2023 in Zhengzhou City provide an ideal opportunity to investigate the effects of such policies and of fireworks burning on air quality during the Spring Festival period. Based on air quality ground-based monitoring data and meteorological data for Zhengzhou City, the article analyzes the impact of the POFB policy and the RHFB policy on air quality. The results show that: (1) The ban on fireworks burning significantly affects Spring Festival air quality, with a decrease of 16.0% in the Air Quality Index (AQI) value in 2016 compared to 2015 and a 74.9% increase in 2023 compared to 2022. (2) From 2016 to 2022, the Spring Festival period witnessed a substantial decrease in average concentration of main pollutants, along with a delayed occurrence of peak concentrations, indicating a noticeable “peak-shaving” effect. However, in 2023, there was an increase in pollutant concentrations, volatility, and a significant surge in hourly concentration. (3) The POFB policy and RHFB policy notably impacted PM2.5 and PM10, with a decrease of 16.1% and 23.6% in PM2.5 and PM10 concentrations, respectively, in 2016 compared to 2015, but an increase of 74.5% and 79.2%, respectively, in 2023 compared to 2022. (4) The contribution of fireworks burning to PM2.5 concentrations significantly decreased during the fireworks burning period (FBP) in 2016 after the POFB policy and increased significantly in 2023 during FBP after the implementation of the RHFB policy. Unfavorable meteorological conditions will undoubtedly exacerbate air quality pollution caused by fireworks burning.